Analisis Yuridis Perbandingan Ketentuan Pendirian Perseroan Terbatas dalam Undang-Undang Cipta Kerja dan Undang-Undang Perseroan Terbatas di Indonesia - Widyari, Dira Putri; Rizka (Universitas Medan Area, 2024)
This research aims to analyze legal conflicts and comparisons in the establishment of Limited Liability Companies (PT) due to changes in regulations accommodated by the Job Creation Law (UU Job Creation). The problem focuses on the Job Creation Law which allows the establishment of a PT without a Notarial deed, only with a statement letter, while the previous Limited Liability Company Law requires at least 2 PT founders to have a Notarial deed in Indonesian. This difference has caused controversy in society. Normative juridical research method by analyzing relevant and conceptual legal regulations. The research results show that although there are significant differences in the regulations for establishing PT, legal dualism does not occur. The Job Creation Law is an amendment to the Limited Liability Company Law creating a more structured and integrated legal framework, reflecting the omnibus law concept which combines various provisions of the Law with various legal topics. In depth understanding of changes in the provisions for establishing PT in Indonesia before and after the Job Creation Law, as well as highlighting the importance of government efforts in creating legal certainty in the world of business and investment.